Triple Approach to Program Evaluation and “Contextual Program Evaluation Model” Proposal - GÜLPINAR, MEHMET ALİ (My University, 2024)
Complexity, contextuality, and reflectivity have come to the forefront in almost every field, including education. In this paper, the program evaluation process is considered within the framework of a socially complex system. In this regard, a model proposal for program evaluation is developed: Contextual Program Evalu-ation Model (CPEM). The conceptual and theoretical frameworks on which the model is based are ‘complexity theory’, ‘contextual/reflective learning and evalu-ation’, and ‘social and ecological/environmental accountability’. Taking this triple framework into account, the four evaluation domains/components of CPEM are as follows: ‘agents’, ‘context-process’, ‘emergent outputs’, and ‘impact’. Consider-ing the core concepts of the complexity system, ‘agents’ is preferred instead of ‘inputs’. Furthermore, since reflective process-orientedness is essential in educa-tion, and the experiences in the process are assumed to be ‘context-dependent’, ‘process-context’ is considered intertwined. Outputs are conceptualized as ‘emer-gent outputs’ because they are viewed as results that emerge through mutual inter-action and transformation within existing patterns and attractors in context-de-pendent reflective processes. Finally, considering the accountability approach, im-pact (institutional/societal/ecological) was identified as the fourth domain of eval-uation. By considering these factors, a program evaluation framework for the CPEM is developed. Then, a concrete example of program evaluation based on CPEM is presented. With this, an attempt has been made to provide users with a helpful guide containing steps.
Keywords: Tıp; Tıp Eğitimi; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Medicine Education; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIBBİ ETİK; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICAL ETHICS; MEDICINE, GENERAL & INTERNAL; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Complexity; contextuality; reflectivity; program evaluation; social accountability